Peningkatan Hasil Belajar Matematika Melalui Media Video Interaktif dengan Model Pembelajaran Problem Based Learning (PBL) Kelas V SDN 2 Bedingin - Kintan Agustina; Anna Mariyani; Fulusia Nurmawati (Paedagogie, 2026)
This study aims to describe the implementation of interactive video media integrated with the Problem Based Learning (PBL) model, to improve students’ learning activities, and to enhance mathematics learning outcomes on the topic of plane figures in Grade V of SDN 2 Bedingin. The research employed Classroom Action Research (CAR) with a cyclical design consisting of planning, action, observation, and reflection stages conducted in two cycles. Data were collected through observation to measure student and teacher activities, tests to assess students’ learning outcomes, and documentation as supporting data. Data analysis was conducted qualitatively to describe the learning process and student activities, and quantitatively to calculate the mean scores and the percentage of learning mastery based on the Minimum Mastery Criteria. The results showed an improvement in both student activities and learning outcomes in each cycle. The percentage of learning mastery increased from 35% in the pre-cycle to 60% in Cycle I, and reached 85% in Cycle II. In addition, students’ learning activities improved from moderately active to active and highly active categories. The implementation of interactive video media combined with the PBL model created a more engaging, interactive, and student-centered learning environment, enabling students to understand plane figure concepts more concretely and meaningfully. In conclusion, the use of interactive video media integrated with the Problem Based Learning model is effective in improving students’ learning activities and mathematics learning outcomes at the elementary school level. This approach can serve as an innovative alternative to enhance the quality of mathematics instruction, particularly for abstract topics.